Effect of Using Sianawai Konasara Application on Motivation and Performance for Employees Education and Cultural Office, North Konawe District - Ansaruddin, Ansaruddin; Abbas, Bakhtiar; Putra, Asrif (PT. Riset Press International, 2024)
The purpose of this study is to explore and analyze the effect of using Sianawai Konasara application on employee motivation and performance at the Office of Education and Culture of North Konawe Regency, as well as to assess the role of motivation as a mediator in the relationship between application use and employee performance. This study involved a total population of 132 state civil apparatus working at the Education and Culture Office of North Konawe Regency, with a random sample of 57 respondents. The data collection method was carried out through questionnaires and data analysis using Partial Least Square (PLS) version 4.0. The results showed that the use of the Sianawai Konasara application had a positive and significant effect on employee motivation and employee performance. Furthermore, employee motivation is proven to significantly influence employee performance and acts as a positive mediator in the relationship between the use of Sianawai Konasara application and employee performance. These findings provide valuable insights for the development of human resource management strategies in the public sector, particularly in the application of information technology to improve employee motivation and performance.